A dynamic localization network for regional navigation under global navigation satellite system denial environments - Hongwei Zhao; Yue Yan; Xiaozhu Shi (International Journal of Distributed Sensor Networks)
Global navigation satellite system signals are easily distorted by the interferences or disturbances, and global navigation satellite system receivers cannot offer continuous effective navigation results in challenging environments. As a representative regional augmentation technology, pseudolite has the potential to provide accurate positioning service to satisfy specific performance requirements in various applications. In this article, we developed a dynamic localization network based on pseudolite technology for regional augmentation navigation purpose. First, the collaborative positioning algorithm is given, and the architecture of localization system is proposed. Then the error sources of localization system are analyzed for performance evaluation. Finally, the proposed system is verified by experiments conducted in both static and kinenatic scenarios. The experiment results demonstrate that the positioning accuracy of the proposed localization system is nearly 10 m, which is close to the global navigation satellite system single-point positioning accuracy. Therefore, it can be used for emergency dynamic positioning of critical areas under the global navigation satellite system denial environments.